PENGARUH MEDIA INSTRUMEN RECYCLE TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATERI POLA RITMIS SD NEGERI 107415 TANJUNG SARI - Sri Rahayu; Putra Afriadi; Irsan; Try Wahyu Purnomo; Sri Mustika Aulia (STKIP Subang, 2026)
ABSTRACT This study aimed to determine the improvement of students’ learning outcomes in music subjects through the use of recycled instrument media. The research employed an experimental method with a One Group Pretest–Posttest design. The population consisted of 33 fifth-grade students of SD Negeri 107415 Tanjung Sari, all of whom were selected as the research sample. The research instrument was a performance skill test assessing aspects of beat and tempo accuracy, rhythmic pattern consistency, playing technique, and students’ self-confidence. The instrument had been tested for validity and reliability. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-Test for hypothesis testing. The results showed that the mean pretest score was 43.56 (low category), while the mean posttest score increased to 76.14 (good category). The normality test indicated that the data were normally distributed, and the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. Based on these findings, it can be concluded that the use of recycled instrument media is effective in improving students’ psychomotor learning outcomes in rhythmic pattern material. This study provides empirical evidence that the implementation of innovative and contextual learning media can significantly enhance students’ skills and understanding. Keywords: Learning Outcomes, Recycled Instrument Media